Pengaruh Penambahan Fly Ash dan Silica Fume terhadap Daya Tahan Penetrasi Air Beton Normal - Ariyadi Basuki (Jurnal Teknologi Bahan dan Barang Teknik, 2015)
In this research a series of tests to determine the characteristics of the composition of concrete with grade fc 30 MPa (normal/control) combined with fly ash additive  (10-15%) or silica fume (5%) of cement weight was conducted. Variation of mixtures are using three different types of admixtures such as type F combined with type G (in trial mix 1) and type D combined with type G (in trial mix 2). The process was continued with the making of cylindrical samples of 15 cm diameter by 30 cm height (compressive strength characteristic), prism samples with the size of 20 cm x 20 cm x 12 cm  (permeability characteristic). Observations were made to know the characteristics of the concrete grade 30 MPa with the addition of additives fly ash or silica fume, compared with normal concrete as a reference, and their application in hot environment. Result of compressive strength value show that mixture with admixtures type D combined with type G has the value of average compressive strength above grade 30 MPa (plan criteria). The addition of fly ash in concrete mix will increase the  compressive strength value up to 1.1% compared to the normal value with water-cement ratio decreases to 0.3 until 0.4 due to the reduction of water content. Mixtures with addition of fly ash or silica fume shows the water penetration value relatively equal compared to normal mixtures, this indicated that concrete products have relatively the same density and can be said to have a fairly good level of durability (penetration value < 5 cm).Pada penelitian ini dilakukan serangkaian pengujian untuk mengetahui karakteristik komposisi rencana beton dengan mutu fc 30 MPa (normal/kontrol) yang dipadukan dengan aditif fly ash 10-15% dan Silica Fume 5% dari berat semen. Variasi campuran menggunakan tiga tipe admixtures yang berbeda yaitu tipe F+tipe G (trial mix 1) dan tipe D+tipe G (Trial mix 2). Proses dilanjutkan dengan pembuatan sampel uji silinder berukuran 15 cm x 30 cm (karakteristik kuat tekan), sampel uji prisma berukuran 20 cm x 20 cm x 12 cm (karakteristik permeabilitas, setting time). Pengamatan dilakukan untuk melihat karakteristik beton fc 30 MPa dengan penambahan aditif fly ash ataupun silica fume, dibandingkan dengan beton normal sebagai acuan, serta aplikasinya dalam lingkungan panas. Hasil kuat tekan memperlihatkan bahwa campuran dengan menggunakan admixtures tipe D+ tipe G memiliki nilai kuat tekan rata-rata diatas kriteria rencana fc 30 MPa. Penambahan fly ash pada campuran beton akan menaikkan nilai kuat tekan sebesar 1,1% dibandingkan beton normal dengan nilai rasio air-semen nya mengecil menjadi 0,3–0,4 karena pengurangan air. Campuran dengan penambahan aditif fly ash atau silica fume menunjukkan nilai penetrasi yang relatif sama bila dibandingkan campuran beton normal, hal ini mengindikasikan produk beton yang terbentuk memiliki kepadatan yang relatif sama dan dapat dikatakan memiliki tingkat durabilitas yang cukup baik (nilai penetrasi < 5 cm).